MARCH7-mediated ubiquitination decreases the solubility of ATG14 to inhibit autophagy - Xue Shi; Wenfeng Wu; Zhenhuan Feng; Peiyang Fan; Ruona Shi; Xiaofei Zhang (Cell Reports, 2023)
Summary: Autophagy is a fundamental biological process critical to all eukaryotic cellular life. Although autophagy has been increasingly studied, how its process is precisely coordinated remains an open question. ATG14 (ATG14L/Barkor) is known to play a crucial role in both autophagosome formation and autophagosome-lysosome fusion. However, how ATG14 is regulated, especially at the post-translation level, is still not clear. Here, we report that MARCH7 (membrane-associated ring-CH-type finger 7), an E3 ubiquitin ligase, inhibits autophagy by ubiquitinating ATG14. MARCH7 significantly promotes K6-, K11-, and K63-linked mixed polyubiquitination on ATG14, triggering the aggregation of ATG14 and reducing its solubility in cells. Functionally, we find that MARCH7 depletion decreases the number of aggresome-like induced structures (ALISs). Mechanistically, we show that ubiquitinated ATG14 has fewer interactions with STX17, leading to the inhibition of autophagy flux. Collectively, our study reveals a mechanism in regulating autophagy and suggests a potential strategy for the treatment of autophagy-related diseases.